The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1073/pnas.0607812104
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous reduction of iron–sulfur protein and cytochrome b L during ubiquinol oxidation in cytochrome bc 1 complex

Abstract: The key step of the protonmotive Q-cycle mechanism of the cytochrome bc 1 complex is the bifurcated oxidation of ubiquinol at the Qp site. It was postulated that the iron-sulfur protein (ISP) accepts the first electron from ubiquinol to generate ubisemiquinone anion to reduce b L. Because of the difficulty of following the reduction of ISP optically, direct evidence for the early involvement of ISP in ubiquinol oxidation is not available. Using the ultra-fast microfluidic mixer and the freeze-quenching device,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 57 publications
1
54
2
Order By: Relevance
“…To get around these problems, we assayed for SQ by rapid freezequench using purified wild-type and mutated cyt bc 1 complex under anaerobic and aerobic conditions. We note that our results are not in contradiction to those of Zhu et al (35), which appeared during revision of our manuscript, because their results were obtained under aerobic conditions in the absence of AA, where we do not expect to observe our SQ species.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…To get around these problems, we assayed for SQ by rapid freezequench using purified wild-type and mutated cyt bc 1 complex under anaerobic and aerobic conditions. We note that our results are not in contradiction to those of Zhu et al (35), which appeared during revision of our manuscript, because their results were obtained under aerobic conditions in the absence of AA, where we do not expect to observe our SQ species.…”
Section: Discussioncontrasting
confidence: 55%
“…Confounding the issue and preventing progress has been the lack of any structural or spectroscopic data on intermediates of the Q o site. Thus far, x-ray structures (2,(30)(31)(32)(33) have not resolved a substrate in the Q o site, earlier reports of SQ intermediates were found to be insensitive to Q o site inhibitors (34), and a very recent rapid freeze-quench study (35) found no evidence for SQ intermediates during the uninhibited turnover of the Q o site. The lack of experimental constraints on the Q o site intermediates has resulted in a proliferation of mechanistic models, including some that posit highly unusual chemistry or that deviate from the Pauling principle of enzymatic activity (i.e., models that invoke destabilized rather than stabilized reactive intermediates) (3).…”
mentioning
confidence: 99%
“…Then the second electron of ubiquinol is passed through the ''low-potential chain'' consisting of cytochromes b L and b H , to reduce ubiquinone or ubisemiquinone bound at the quinol reduction site (Qn) [13,14]. Pre-steady state kinetic analysis of cytochrome b L and ISP indicates that both are reduced by ubiquinol at the same rate and the reduction of b H occurs before the reduction of cytochrome c 1 [15][16][17][18]. Since the reduction of ISP by QH 2 takes place when the head domain of ISP is located at the b-position, a movement of head domain to the c 1 -position is necessary for transfer electron to cytochrome c 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the reduction of ISP by QH 2 takes place when the head domain of ISP is located at the b-position, a movement of head domain to the c 1 -position is necessary for transfer electron to cytochrome c 1 . It was speculated that protein conformational changes caused by electron transfer from cytochrome b L to b H facilitates the movement of the head domain of ISP [18][19][20]. This speculation is supported by the fact that reduction of cytochrome b H occurs before the reduction of cytochrome c 1 [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…One drawback of this sequential scheme is the lack of a "functional" semiquinone at the ubiquinol oxidation site (Q P ) (12)(13)(14), even though some radicals have been reported under abnormal conditions (15,16). Recently, pre-steady-state kinetic analysis of the reduction of cytochrome b L and the Rieske ironsulfur protein in the same sample using fast quenching coupled with EPR (17) indicated that both the iron-sulfur cluster and heme b L are reduced by ubiquinol at the same rate, suggesting a concerted scheme for the bifurcated oxidation of ubiquinol at the Q P site (18,19).…”
mentioning
confidence: 99%